2021
DOI: 10.24874/ti.995.10.20.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 and CuO Based Nanolubricants on the Static Thermal Performance of Circular Journal Bearings

Abstract: Circular journal bearings constitute the heart of power generation equipments due to their simple design, ease in manufacturing and high loadcarrying capacity. Hydrodynamic action in these bearings is manifested by the presence of a single oil film, which increases the oil film temperature at higher loads. However, in order to improve the performance of bearings and for overall optimization of equipment efficiency, lubricants with specialized additives are being explored. With the advancements in nanotechnolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…5 Engineering colloids are dispersed in traditional lubricants with a limited amount of nano-sized materials, such as nano-fibres, nano-sheets, nanoparticles, and nano-rods, to achieve a stable dispersion of these materials. The use of nanolubricants in a variety of disciplines, including the automotive, 6 machining, 7 aerospace, 8 thermal power generation, 9 and micro/nano-electromechanical systems (MEMS/NEMS) 10 has recently piqued the interest of multiple research groups.…”
Section: Introductionmentioning
confidence: 99%
“…5 Engineering colloids are dispersed in traditional lubricants with a limited amount of nano-sized materials, such as nano-fibres, nano-sheets, nanoparticles, and nano-rods, to achieve a stable dispersion of these materials. The use of nanolubricants in a variety of disciplines, including the automotive, 6 machining, 7 aerospace, 8 thermal power generation, 9 and micro/nano-electromechanical systems (MEMS/NEMS) 10 has recently piqued the interest of multiple research groups.…”
Section: Introductionmentioning
confidence: 99%
“…These particles are made of metals, metal oxides, silicates, semiconductors and carbonates [9][10][11][12]. Researchers have investigated the effect of different types of nano-lubricants [13][14][15][16][17][18][19][20][21][22][23] with varying concentrations of nano-additives [14,19,[24][25][26] on the performance of the bearing. Figure 1 shows different nano-particles applied in fluid film lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…To anticipate the bearing performance, Mansoor et al [5] simulated three-dimensional model of journal bearing using various parameter like load carrying capacity, wall shear stress, static pressure, etc. Recently, Dang et al [6] studied circular journal bearing considering staticthermal performance of TiO2 and CuO based nanolubricants and observed that nano-lubricants increases load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%